Intravenous liposomal amphotericin B efficacy and safety for cutaneous and mucosal leishmaniasis: a systematic review and meta-analysis protocol. Issue 6 (16th June 2021) - Naeem, Faheel; Nathan, Keren; Chivinski, Jeffrey; Ekmekjian, Taline; Libman, Michael; Barkati, Sapha
Abstract : Introduction: Treatment of cutaneous and mucosal leishmaniasis (CL and ML, respectively) must be individualised as there is no universal therapeutic approach. Intravenous liposomal amphotericin B (L-AmB) is an accessible and relatively safe treatment that has been increasingly used for the treatment of CL and ML. While several descriptive studies have been published on the efficacy and safety of L-AmB, there are no interventional studies. Moreover, the findings from published studies have not yet been integrated and synthesised. Therefore, we aim to evaluate and consolidate the descriptive evidence on the efficacy and the safety of Intravenous L-AmB treatment for CL and ML in both the New and Old World. Methods and analyses: A systematic review of all relevant study types with no restriction on date or language of publication will be conducted. Online databases including MEDLINE, The Cochrane Library, EMBASE, EBSCO, Scopus, Ovid and WHO databases were searched on 3 April 2020. The search included all study types that assess Intravenous L-AmB treatment for CL and ML in humans. The Population, Intervention, Comparison, Outcome and Study Design strategy and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines will be used to determine which studies will be selected for final inclusion. The quality of included case series and case reports will be assessed using modified quality assessment tools. A narrative synthesis of the findings will be provided and the primary outcome and secondary outcome of interest, response rate and adverse events rate, respectively, and the 95% CI will be ascertained. Estimates from individual studies will be pooled using random-effects model. Ethics and dissemination: This systematic review does not require formal ethical approval since no primary data will be collected. Findings will be disseminated through a peer-reviewed publication and relevant conferences. PROSPERO registration number: CRD42020173440.